Cultural and ethnobotanical legacy of native potatoes in Colombia - Daicy Yaneth Galvis-Tarazona; Zaida Zarely Ojeda-Pérez; Diana Marcela Arias-Moreno (BMC, 2022)
Abstract Background Native potatoes are Andean tubers of great historical, social, food, genetic and nutritional importance, and they contribute significantly to food security by supplementing the household diet and also providing alternative income. Even when their cultivation and consumption imply great benefits, their use and local preservation depend to a large extent on the recognition of their ethnobotanical and cultural importance. In this context, this study consolidates an important ethnobotanical research bases for native potatoes in Colombia. Methods The study collected data through semi-structured interviews and dialogues (130) in the municipality of Chiscas, department of Boyacá, central-eastern Colombia. The questionnaire was focused on native potatoes and sought to investigate the knowledge related to cultivation, diversity, patterns and forms of preparation for use and consumption. Likewise, knowledge heritability mechanisms were investigated and ethnobotanical indices of relative importance, use and culture were estimated. Results Documentation of ethnobotanical knowledge included aspects such as seed care and availability, cultural management of the crop, patterns of use and consumption, as well as ways of preparing the tubers. In total, 23 vernacular names of native potato and 360 reports of use (commercial, domestic or ritual-magical) were recorded for the 15 main genotypes. Quantitative estimates included the importance index: (a) cultural, for which values ranged between 0.059 and 0.812; (b) relative, with records between 0.04 and 0.43; and (c) use, which ranged between 0.06 and 0.63. The ethnobotanical importance index (d) for native potatoes was 57.26, which corresponds to a "very high" ethnobotanical value. This allowed us to identify that Criollas were the most recognized and used potatoes within the community. In addition, it was shown that vertical transmission is the main way in which traditional knowledge about native potatoes is inherited. Finally, an artificial intelligence tool was preliminarily implemented to identify the polarity generated in the interviewees by the questions. Conclusion The results of this research provide valuable information on the ethnobotany of native potatoes in Colombia. The genotypes used by the community of the municipality of Chiscas were recognized for their high gastronomic and nutritional potential, as well as for their great ethnobotanical and cultural importance. These data can be considered as a valuable tool to support any action aimed at the conservation and revaluation of these tubers.